Clinical Profile and Prescription Patterns in Culture-proven Enteric Fever in Children - Divya Priyadharshini; Mobill Clinton; Nandini Sethuraman; Mathrubootham Sridhar; Vidya Krishna (Pediatric Infectious Disease, 2024)
Aim: We aimed to study the clinical profile of enteric fever in children at an urban tertiary care children's hospital in South India. Materials and methods: We carried out a retrospective study of culture-proven enteric fever in children aged 0–18 years between January 2018 and March 2023. We included 128 children in total; 109 inpatients (85.2%) and 19 outpatients (14.8%). Results: Enteric fever accounted for 4.9% of nonrespiratory febrile admissions (n = 2,204). A total of 98 (76.5%) had Salmonella typhi (S. typhi), while 30 (23.5%) had Salmonella paratyphi (S. paratyphi) A in their blood. Leukopenia occurred in 28 (21.8%) patients. The average inpatient fever defervescence time was 4.62 days (range: 1–28 days). A total of 26 children (20.3%) experienced fever defervescence after 5 days. The mean C-reactive protein (CRP) was 58.2 mg/dL in the group with fever defervescence in <5 days and 63.3 mg/dL for >5 days (p = 0.540). Single antibiotic was used in only 25 children (19.5%). Mean fever defervescence time was 4.8 days in the single antibiotic group and 4.5 days in the combination group (p = 0.47), and in typhoid vs paratyphoid, it was 4.8 vs 3.3 days (p = 0.04). Conclusion: Salmonella paratyphi (S. paratyphi) caused 23.5% of culture-proven enteric fever cases. Most cases had normal leukocyte counts, eosinopenia, and elevated CRP. CRP does not predict fever defervescence. Fever typically resolved in 4–5 days, with paratyphoid fever resolving earlier. Combination therapy was used in over two-thirds of cases. Clinical significance: Salmonella paratyphi (S. paratyphi) is a significant cause of enteric fever in children. There seems to be no clear benefit for combination therapy from our small retrospective data, but study limitations preclude drawing accurate conclusions. Future areas of research interest will include an effective vaccine for paratyphoid fever and a randomized clinical trial on single vs combination therapy in enteric fever.